The Role of Education in Preventing E-Smoking Behavior is to Increase Student Knowledge and Attitudes - Sri Sunarti; Tukimin bin Sansuwito; Purwo Setiyo Nugroho; Nida Amalia; Rusni Masnina; Linda Suwarni (Journal of Public Health and Pharmacy, 2024)
Introduction: Aim this reseach to determine the differences in levels of knowledge, Attitude about e-smoking prevention before and after education between ekperimental and the control group the Samarinda City Central Statistics Agency in 2017 (3). The number of teenage smokers in the city of Samarinda reached 29.69%. While there is a significant level of access to advertisements for cigarettes on television and the internet, 15.7% of people access the internet, and 41.5% of people access electronic cigarettes with their peers. Methods: The experimental design of this study consisted of a two-group experimental design with a pre-test and a post-test plus a control, with the purpose of determining the impact of educational intervention through the use of web-based preventive education for mesuare diffrences knowled and attitude Results: The Different Tests Within Experiment Group Of Knowledge, Attitudes From One Month After Intervention, knowledge P-Value 0.000, Attitudes P-Value 0,00. The Different Tests Within Control Group Of Knowledge, Attitudes From One Month After Intervention, Knowledge P-Value 0,97 and attitudes P-Value 0,135. Conclusion: After the education was carried out, the results demonstrated that there were differences in the experimental group's knowledge and attitudes before and after the education was carried out. The control group did not exhibit any differences in knowledge or attitudes during either of the two measures that were conducted. It was found that there were variations in knowledge and attitudes between the experimental group and the control group after one month of post-education was delivered.